Otolith morphology and body size relationships of Monopterus albus in Malaysia - Ahmad Syazni, Kamarudin; Norshida, Ismail; Aliyu Garba, Khaleel; Syafiq Aiman, Mohd Nasir; Radhiah, Kasumen (2019)
Monopterus albus production in Malaysia is widely depends on wild stock. Otolith morphology has been widely used to give additional information that is crucial for aiding the seed production. Otolith morphology of Asian swamp eel, Monopterus albus and its relationships to fish size was examined. A total of 125 samples were collected from the East Coast of Peninsular Malaysia (ECPM) and Sabah for analyses. Otolith descriptions were based on its outline, including otolith length (OL, mm), otolith height (OH, mm) and otolith weight (OW, mm). Fish total length (TL, cm) and body weight (BW, kg) were also measured and recorded. Paired t-test result (p-value > 0.05) showed there is no statistically significant difference between left and right otolith dimensions. Regression models related to otolith morphometric parameters with eel length and body weight were determined. There is no morphological difference between left and right otolith of swam eel observed. Otolith weight is a good indicator of body weight (R2 =0.8994) and total length of fish (R2 =0.8707) since the R2 value is strongest than other relationship. If the otolith weight used to estimate the length and body weight of eel, the regression explains more than 87% of data variation in this Monopterus albus.